Poor sleep quality indirectly contributes to higher sexual risk-taking by increasing the likelihood of engaging in substance use among LGBTQ+ individuals - Sarı, Efe; Durdu, Nevin; Ay, Beril; Sancak, Barış (Frontiers in Psychiatry, 2025)
BackgroundPoor sleep quality (PSQ) is disproportionately prevalent among LGBTQ+ individuals and has been linked to substance use, sexual dysfunction and sexual risk-taking (SRT). However, the interplay between sleep health, substance use, SRT, and sexual dysfunction remains underexplored in diverse LGBTQ+ populations. This study investigates whether substance use mediates the relationship between PSQ and SRT among LGBTQ+ individuals in Turkey.MethodsA cross-sectional survey, using snowball sampling was conducted among 249 LGBTQ+ individuals in Turkey. Measures included the Pittsburgh Sleep Quality Index (PSQI), Index of Sexual Risk-Taking (ISRT), Arizona Sexual Experiences Scale (ASEX), AUDIT-C for alcohol use, and self-reported recent substance use. Logistic and linear regression analyses were used to assess associations between PSQ, substance use, and SRT. Mediation analysis was conducted using structural equation modeling (SEM).ResultsPSQ was highly prevalent (80.7%) and significantly associated with alcohol use and chemsex-related substance use (CRSU). CRSU was strongly linked to increased SRT (β = 1.489, p <.001) and served as a significant mediator in the PSQ-SRT relationship (β = 1.045, p = .047). No significant mediation effect was found for alcohol use.ConclusionPoor sleep quality indirectly contributes to higher sexual risk-taking among LGBTQ+ individuals by increasing the likelihood of engaging in chemsex-related substance use. These findings highlight the need for integrated public health interventions addressing sleep health, substance use, and sexual risk-taking in LGBTQ+ communities, particularly in settings with rising substance use rates.